Use of airborne Lidar to investigate mangrove accommodation space in macrotidal estuaries of northern Australia. (30th October 2020) - Woodroffe, Colin D.; Kumbier, Kristian; Rogers, Kerrylee
Abstract: Extensive mangroves in the Northern Territory of Australia reflect the large tidal range along that coast. Airborne Lidar enables interpretation of ground elevation along transects through mangroves and across coastal and estuarine plains, supplementing past levelling surveys of elevation range of the principal mangrove taxa. Mangrove distribution in the upper intertidal varies geographically in response to tidal variations. In the well-mapped Darwin and Bynoe Harbours, Sonneratia alba grows at elevations below mean sea level, whereas Rhizophora occupies a prominent zone that is inundated by neap tides. Ceriops is generally found at higher elevations, often showing a canopy height gradation. A number of mangroves, including Avicennia, occur at the upper bound of the mangrove forest adjacent to the hinterland, which occurs at 2.8 m above Australian Height Datum (AHD) on the open coast and at 3.6 m AHD, reflecting tidal amplification, in the embayments. Along the less known macrotidal estuaries of the Alligator Rivers, accommodation space and species distribution varies with distance from the open coast. On the coastal plain that has formed along the southern margin of van Diemen Gulf, Lidar reveals that landwardmost mangroves also occur up to an elevation of 2.8 m AHD. Amplification of tides in the cuspate-meandering middle sections of the South and East Alligator Rivers enables mangroves to occur up to 3.5–3.6 m AHD, in contrast to the less infilled West Alligator River. The Lidar reveals substrate topography and vegetation structure. The Rhizophora zone is particularly distinct and its steeper gradient implies rapid sediment accretion; Rhizophora has played a disproportionately large role in the sequestration of blue carbon. Low-lying parts of these estuarine plains, particularly former channels, are already experiencing tidal creek extension and saline intrusion, and topography of the landscape behind the mangroves will mean many areas will be vulnerable to future salinization in response to rising sea level. Highlights: Airborne Lidar data reveals mangrove ground topography and vegetation structure. Lidar data independently verifies earlier surveys in macrotidal northern Australia. Mangroves reach higher elevation in Darwin and Bynoe Harbours than on open coasts. Mangrove distribution also responds to tidal amplification along the Alligator Rivers. Complex topography affects vulnerability of estuarine plains to future sea-level rise.